2006
DOI: 10.1111/j.1440-1711.2005.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular, molecular and immunological mechanisms in the pathophysiology of vein graft intimal hyperplasia

Abstract: Summary Coronary artery disease, leading to myocardial infarction and ischaemia, affects millions of persons and is one of the leading causes of morbidity and mortality worldwide. Invasive techniques such as coronary artery bypass grafting are used to alleviate the sequelae of arterial occlusion. Unfortunately, restenosis or occlusion of the grafted conduit occurs over a time frame of months to years with a gradual reduction in patency, especially in vein grafts. The events leading to intimal hyperplasia (IH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
127
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 142 publications
3
127
0
4
Order By: Relevance
“…These inflammatory factors, including transforming growth factor-b (TGF-b), platelet derived growth factor (PDGF), basic fibroblast growth factor (bFGF) and vascular cell adhesion molecule (VCAM) may lead to proliferation and migration of vascular smooth muscle cells, intimal hyperplasia and induction of mononuclear and macrophage inflammatory infiltration or conversion into foam cells. This complex process ultimately results in atherosclerotic plaque formation and luminal stenosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inflammatory factors, including transforming growth factor-b (TGF-b), platelet derived growth factor (PDGF), basic fibroblast growth factor (bFGF) and vascular cell adhesion molecule (VCAM) may lead to proliferation and migration of vascular smooth muscle cells, intimal hyperplasia and induction of mononuclear and macrophage inflammatory infiltration or conversion into foam cells. This complex process ultimately results in atherosclerotic plaque formation and luminal stenosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the ADAMs family (ADAM 8,9,10,12,15,17,19 and 28) are expressed widely in epithelial cells, smooth muscle cells and leukocytes [3,4]. As a well-known ectodomain sheddase, ADAM17 plays an important role in vascular physiological and pathological processes through regulating membrane-anchored protein maturation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, pathological intimal hyperplasia (IH) ensues after these procedures largely due to the proliferation of vascular smooth muscle cells (VSMCs) in the media and their migration into the intima of the treated vessel (1)(2)(3). Such proliferation is induced by a number of growth-stimulatory signals that are activated by vascular injury and leads to high long-term failure rates of bypass surgery and angioplasty for treatment of cardiovascular disease (4)(5)(6)(7)(8)(9)(10)(11)(12). These failures often cause death and disability and may require repeated treatment by surgery or angioplasty.…”
mentioning
confidence: 99%
“…It has been shown that the level of intimal hyperplasia is directly linked to the degree of endothelial denudation, which, in vein grafts is caused by luminal distension during surgery, ischemia, damage at surgical anastomoses and continued physical trauma under arterial conditions (2)(3)(4). Moreover arterial tangential pressure, medial damage and thickening as well as shear stress changes and altered fl ow patterns are involved in the development of intimal hyperplasia (5)(6)(7).…”
mentioning
confidence: 99%